To solve the quadratic equation \(x^2 + 2x - 8 = 0\) by completing the square, follow these steps:
-
Rearrange the equation: Move the constant term to the other side: \[ x^2 + 2x = 8 \]
-
Complete the square: Take the coefficient of \(x\), which is 2, halve it to get 1, and then square it to get 1. Add this square to both sides: \[ x^2 + 2x + 1 = 8 + 1 \] This simplifies to: \[ (x + 1)^2 = 9 \]
-
Take the square root of both sides: \[ x + 1 = \pm 3 \]
-
Solve for \(x\):
- For the positive case: \[ x + 1 = 3 \quad \Rightarrow \quad x = 2 \]
- For the negative case: \[ x + 1 = -3 \quad \Rightarrow \quad x = -4 \]
Thus, the solutions to the equation are: \[ x = 2, \quad x = -4 \]
Therefore, the correct answer is: x=2, x=−4